PENGARUH STRES KERJA, KONFLIK KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA UPTD PUSKESMAS SUKAWATI II KABUPATEN GIANYAR - Iluh Devi Puspa Wati; I Gede Rihayana; Bagus Nyoman Kusuma Putra (VALUES, 2023)
Performance is the result of work performance in the form of both quality and quantity achieved by human resources per unit time in carrying out their work duties in accordance with the responsibilities given to them. factors that can affect employee performance include work stress, work conflict, and work discipline. This study aims to determine the effect of work stress, work conflict, and work discipline on employee performance at UPTD Puskesmas II Gianyar Regency. The location of this research is UPTD Puskesmas Sukawati II Gianyar Regency which is located at Jl.Kesawa No.1, Singapadu Kaler, Kec. Sukawati, Gianyar Regency. The objects examined in this study are work stress, work conflict, work discipline, and employee performance. The population in this study was all employees of the Sukawati II Health Center, Gianyar Regency, totaling 72, determining the number of samples used by the authors in this study using the census method based on the provisions put forward by Sugiyono (2017), who said that "saturation sampling is a sampling technique when all members of the population are used as samples. Another term for saturated sample is census. The data analysis technique used is multiple linear regression analysis. The results showed that work stress, work conflict, and work discipline had a negative and significant effect on employee performance at the UPTD Puskesmas Sukawati II, Gianyar Regency.